Dinamika Kinerja Keuangan dan Opini Audit Going Concern pada Perusahaan Manufaktur yang Terdaftar di BEI - Setiawati, Luh Pande Eka; Dewi, Kadek Indah Kusuma (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The existence of the capital market requires companies to undergo independent audits conducted by a Public Accounting Firm (KAP) that has obtained permission from the Minister of Finance and is trusted by the company. Auditors must carefully evaluate the company’s situation so that the audit report reflects the true condition of the company and does not mislead investors. A going concern audit opinion is the auditor's assessment of a company's ability to continue its operations. Factors influencing the going concern audit opinion include profitability, liquidity, leverage, company size, and company growth. This study aims to analyze and provide empirical evidence regarding the influence of profitability, liquidity, leverage, company size, and company growth on the going concern audit opinion. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the period of 2020-2022, with a sample of 153 companies selected using purposive sampling. The data were analyzed using logistic regression. The results show that company size has a negative effect on the going concern audit opinion, while factors such as profitability, liquidity, leverage, and company growth do not significantly influence the going concern audit opinion. Future studies are recommended to expand the sample size and include additional relevant variables.